Research progress on the pathogenesis of Graves’ ophthalmopathy: Based on immunity, noncoding RNA and exosomes - Zheng, Jingyi; Duan, Honghong; You, Sufang; Liang, Bo; Chen, Yuping; Huang, Huibin (Frontiers in Immunology, 2022)
Graves' ophthalmopathy (GO), also known as thyroid-associated ophthalmopathy, is a common potentially vision-threatening organ-specific autoimmune disease and the most common extrathyroidal manifestation of Graves' disease. It can happen to those who have hyperthyroidism or euthyroidism. At present, the pathogenesis of GO has not been fully elucidated, and the majority of clinical treatments are symptomatic. Therefore, we are eager to discover any new therapeutic strategies that target the etiology of GO. To provide fresh ideas for the creation of new therapeutic techniques, this study primarily discusses the research state and progress of GO-related pathogenesis from the perspectives of GO's cellular immunity, autoantigens, non-coding RNAs, and exosomes.